Changes in Expression of the CLOCK Gene in Obstructive Sleep Apnea Syndrome Patients Are Not Reverted by Continuous Positive Airway Pressure Treatment - Moreira, Susana; Rodrigues, Raquel; Barros, André B.; Pejanovic, Nadja; Neves-Costa, Ana; Pedroso, Dora; Pereira, Cláudia; Fernandes, Dina; Rodrigues, João Valença; Barbara, Cristina; Moita, Luís Ferreira (Frontiers in Medicine, 2017)
Purpose: Metabolic syndrome and cardiovascular disease are strongly associated with obstructive sleep apnea syndrome (OSAS), which causes substantial changes to normal circadian physiological functions, including metabolic pathways. Because core clock genes are known to be modulated by sleep/vigilance cycles, we asked whether the expression level of mRNA coding for clock genes is altered in non-treated OSAS patients and if it can be corrected by standard positive pressure treatment. Methods: Peripheral blood was collected from male patients diagnosed with severe OSAS (AHI≥30/hr) before and after treatment initiation. qPCR was used to measure mRNA levels of genes associated with the central circadian pacemaker including CLOCK, Bmal1, Cry1, Cry2 and three Period genes (Per 1, 2, 3) in peripheral blood mononuclear cells (PBMCs). Results: We found statistically significant differences for CLOCK (p-value=0.022) expression in PBMCs of OSAS patients that were not reverted by treatment with standard positive pressure treatment. We have also found a substantial decrease in the slow wave sleep (SWS) content in OSAS patients (p-value<0.001) that, contrary to REM sleep, was not corrected by CPAP (p=0.875). Conclusions: CPAP treatment does not correct substantial changes in expression of core clock genes in OSAS patients. Because CPAP treatment is also unable to normalize the SWS in these patients, it is likely that additional therapeutic interventions that increase SWS content and complement the benefits of CPAP are required to more effectively reduce the known increased cardiovascular risk associated with OSAS patients.